Desenvolvimento de uma sequência didática para o ensino de concepções sobre estrutura atômica e periodicidade química nas séries finais do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2020)
This work presents the results of the application of a teaching sequence (TS) to a Elementary School II ninth grade class of Colégio Nossa Senhora Auxiliadora, part of Salesian School network, a private institution in the city of Bagé - RS. In order to develop, implement and evaluate teaching activities to address topics of atomic structure and chemical periodicity, mediated by a mobile application and a virtual teaching and learning environment. For the implementation of SD, the author developed a mobile application for the dissemination of content and teaching materials, together with a virtual Google Classroom teaching and learning environment. A logbook was built by the students to record the resolution of the didactic units presented by the teacher, as well as a concrete lapbook material after the SD implementation. Students' performance was quantitatively evaluated according to the method of normalized learning gain through pre- and post-tests containing objective questions about all the content worked on. Students' visual and textual productions in lapbooks and logbooks were qualitatively analyzed. Visual and / or textual elements were sought in these two materials that would provide evidence of how the students made the landscape crossings recommended by the TFC. As main results, the class presented a normalized learning gain of 54.31%, which is considered a very good result. It was also possible to observe some evidence of how the students constructed their conceptions about structure of matter and periodic laws by analyzing the concrete materials.
Keywords: Ensino de química; Teoria da Flexibilidade Cognitiva; Aplicativos móveis; Ambientes virtuais de ensino e aprendizagem; Chemistry teaching; Flexible Cognitive Theory; Mobile applicatives; Virtual learning and Teaching environment; CNPQ::CIENCIAS SOCIAIS APLICADAS